Combating Ethnic Xenophobia through Digital Pedagogy: The Development of a TIDAYU Local Wisdom-Based Interactive E-Book in Multiethnic Schools - Mertika Mertika; Dewi Mariana; Asmadi Asmadi; Aan Khosihan (Jurnal Pendidikan Progresif, 2026)
This study aims to develop and evaluate an interactive e-book based on the local wisdom of Tionghoa, Dayak, and Malay (TIDAYU) as a learning medium to enhance cultural literacy and reduce ethnic xenophobia among elementary school students in Singkawang City. The study is expected to produce a pedagogical model that integrates digital media and cultural values to promote inclusive and tolerant learning and serve as a potential solution for multicultural education grounded in local wisdom. The research employed a Research and Development (R&D) approach, using a modified Borg and Gall model comprising six stages: needs analysis, design, development, validation, implementation, and evaluation. The participants were 75 fifth-grade students from three elementary schools representing the major ethnic groups and regions of Singkawang (North, Central, and West Singkawang). Data were collected through expert validation sheets, teacher and student response questionnaires, and pre-test and post-test instruments on cultural literacy and tendencies toward xenophobia. Data analysis was carried out using non-parametric descriptive and inferential statistics (Friedman test and pairwise comparisons). The validation results showed that e-books were rated "very valid" (average 81%) and "very practical" (average 84%). Learning implementation is also high, averaging 85%. The Friedman test showed a significant difference (p < 0.001) between pre- and post-test scores across regions, indicating an increase in cultural literacy and a decrease in xenophobia following e-book use. The post-test results across schools showed consistent effectiveness. It can be concluded that TIDAYU interactive e-book has successfully integrated local wisdom into digital learning, fostering cross-cultural understanding, empathy, and tolerance in a multiethnic environment. This product contributes theoretically to the development of multicultural learning media based on local culture, as well as providing practical guidance for teachers in realizing inclusive basic education rooted in regional culture. Keywords: interactive e-book, cultural literacy, TIDAYU, local wisdom, xenophobia, multicultural learning.